Finite Difference Method in Regular Geometry Heat Transfer Problem - Ngarisan, Noor Syazana; Ab. Aziz, Amiruddin (Journal of Ocean, Mechanical and Aerospace -science and engineering-, 2019)
Finite difference method (FDM) is a known numerical method for finding approximate solution to boundary value problems (BVP). It is a helpful method in approximating the solutions to differential equation. Numerical methods are very useful in solving engineering problems in many areas related to fluid dynamics, heat and mass transfer problems and other partial differential equations of mathematical physics especially when such problems cannot be solved numerically due to nonlinearities, complex geometries or complicated boundary conditions. However, the application is limited to regular geometry and simple irregular geometry problems.